2023
DOI: 10.1002/jclp.23477
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting to a new reality: Consensual qualitative research on therapists' experiences with teletherapy

Abstract: Objective In the wake of the COVID‐19 pandemic, the use of teletherapy has become more pervasive than ever. Many therapists faced this move to a remote setting with little experience or training. We aimed to qualitatively examine therapists' subjective experience of providing teletherapy, including changes in technique, the therapeutic relationship, and the therapeutic process. Methods Thirty‐one psychotherapists participated in semistructured interviews. Interviews were recorded, then transcribed and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Although the impact of the Covid-19 pandemic on helping professionals-in-training has been the focus of many recent studies, the interest in psychotherapists in training remains largely a peripheral part of larger quantitative studies [ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] ]. What can generally be said is that therapists were overwhelmed and thus felt insecure in their professional role and clinical work [ [12] , [13] , [14] , [15] , [16] , [17] ]. Everyone, including psychotherapists, was influenced by this experience in their private and professional lives [ [18] , [19] , [20] , [21] , [22] , [23] ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the impact of the Covid-19 pandemic on helping professionals-in-training has been the focus of many recent studies, the interest in psychotherapists in training remains largely a peripheral part of larger quantitative studies [ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] ]. What can generally be said is that therapists were overwhelmed and thus felt insecure in their professional role and clinical work [ [12] , [13] , [14] , [15] , [16] , [17] ]. Everyone, including psychotherapists, was influenced by this experience in their private and professional lives [ [18] , [19] , [20] , [21] , [22] , [23] ].…”
Section: Introductionmentioning
confidence: 99%
“…Therapists noted that they had become more open and willing to share their personal experiences compared to their in-person practice ( Mitchell, 2020 ). Similarly, some therapists (as well as patients, see Shtrackman, Békés et al, 2023 ) reported a sense of connecting more as humans besides professional and patient, and letting patients see more of them as persons ( Békés et al, 2023 ). Some therapists reported that they used self-disclosure as a tool to compensate for the physical distance, especially when supporting patients during a time of global distress ( Nuttman-Shwartz and Shaul, 2021 ; Aafjes-Van Doorn et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, therapists also reported several challenges in teletherapy. For example, therapists noted that the teletherapy sessions often feel less deep emotionally and more superficial, and the teletherapy setting pulls them to provide support and counseling rather than engaging in a more open-ended exploration of the patients’ inner world ( Békés et al, 2023 ). Therapists often attempted to compensate for this by becoming more active and directive, and avoiding silences in teletherapy sessions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For therapists, conducting sessions from their home may involve more (willingly or unwillingly) TSD, which may shift therapists' perceptions of the therapeutic relationships. While post‐pandemic research is needed to differentiate the impact of the global, shared stressor of the pandemic and that of the therapy format on the increased real relationship, evidence suggests that this sense of authenticity and egalitarian approach may benefit patients and the therapeutic process (Békés et al, 2023), yet also knowing that TSD is not always beneficial (Hill et al, 2018). It can thus be challenging for therapists to navigate therapeutic actions involving authenticity and self‐disclosure.…”
Section: Introductionmentioning
confidence: 99%